Optimization of micro EDM drilling process using Taguchi method - Yazid, Yahya (2009)
This thesis deals with optimization of micro Electrical Discharge Machining (EDM) drilling process using Taguchi method. EDM is a thermal process that utilizes spark discharges to erode a conductive material. The objective of this thesis is to study the effect of independent variable to accuracy of micro EDM drilling process and to optimize it by using Taguchi method. Taguchi Method is used to find the optimal drilling parameters for hole diameter in drilling operation. The orthogonal array, the signal-to-noise ratio, and analysis of variance are employed to study the performance characteristics in drilling operations of mild steel (50mm length x 75mm width x 5mm height) as workpiece by using 1mm copper (Cu) pipe electrode. Three drilling parameters namely, pulse off time, peak current, and servo standard voltage, are optimized with considerations of hole diameter. It is found that Taguchi’s robust orthogonal array design method is suitable to analyze the hole diameter problem. Also parameter design of Taguchi method provides a simple, systematic and efficient methodology for the optimization of drilling process. The result concluded that use of greater pulse off time, greater peak current and medium servo standard voltage give the better hole diameter for the specific test range. The results also significantly reduce the cost and time market and improve product reliability and customer confidence. There are several suggestions that could be implanted as to improve results and obtained more accurate finding. For example, the experiment should be run repeatedly in order to gain more accurately ANOVA table. In addition, further study could consider more factor such as pulse on time, material removal rate (MRR), coolants and etc in the research to see how the factors would affect hole diameter.